PENGARUH KOMPETENSI DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP PRESTASI KERJA KARYAWAN PADA KOPERASI MERTA RAUH DESA SEDANG BADUNG - Gupta, I Gusti Bagus Wirya; Dwipayana, I Made (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2024)
Every company always strives so that employees involved in company activities can provide the highest work performance possible to realize the goals that have been set. The formulation of the problems in this study are: 1) Does competence have a partial effect on employee performance at the Merta Rauh Cooperative, Sedang Village, Badung Regency? 2) Does transformational leadership have a partial effect on employee performance at the Merta Rauh Cooperative, Sedang Village, Badung Regency? 3) Does competence and transformational leadership simultaneously effect on employee performance at the Merta Rauh Cooperative, Sedang Village, Badung Regency? Data were analyzed using multiple linear regression analysis. The results showed: 1) Competence has a positive and significant partial effect on employee performance at the Merta Rauh Cooperative, Sedang Village, Badung Regency. 2) Transformational leadership has a positive and significant partial effect on employee performance at the Merta Rauh Cooperative, Sedang Village, Badung Regency. 3) Competence and transformational leadership have a positive and significant simultaneous effect on employee performance at the Merta Rauh Cooperative, Sedang Village, Badung Regency.